India's Role in the Legal Regulation of Private Actors in Space. Issue 2 (1st September 2016) - Adhikari, Malay
ABSTRACT: Today, India enjoys the status of a spacefaring state. It is the national space agency—the Indian Space Research Organization—which created the culture of self-reliant space technology through its space program achievements. Even though there are emergent private actors in addition to the national space agency, it is very difficult to realize their potential in space in India. Because the national space program is societal-centric and application-centric, space commercialization is constrained. Nevertheless, there is interest in overcoming these constraints and in enabling a role for private space actors in India. In such a scenario, legal regulations are required. Within this context, is the existing legal regulatory framework sufficient, and has India already considered a vital role to regulate private actors in space? Also, are there global influences? This article analyzes these queries.